POLISH JOURNALISTS’ REPORTS ABOUT MOLDAVIAN SSR, 1978–1984 - Marius TĂRÎȚĂ (Academy of Sciences of Moldova, 2021)
The article addresses the subject on the interest shown by Polish journalists towards the Moldovan SSR in years 1978–1984. Evocative texts in this regard were published in the articles from “Polityka”, “Trybuna Ludu”, “Kraj Rad”, “Przyjaźń” and “Dziennik Ludowy” newspapers and magazines. References to specific topics related to the Moldovan SSR also appeared in the internal news bulletins of the Polish Press Agency. The present study is divided into three. In the first part, there are reflected articles containing personal (sometimes lyrical) opinions of journalists who visited the republic (E. Gajda, A. Strońska, M. Porajska). The second part highlights the official communiqués dedicated to political, ideological or economic events. In addition, interviews with secretaries of the Central Committee of the Communist Party and with the chief executive of the Moldovan SSR are revealed. The third part examines the analysis by the Polish Press Agency of a possible conflict between Moscow officials and the Republican party leadership in December 1983–February 1984.